TEACHERS AS SOCIAL MEDIATORS IN DEVELOPING AUTISTIC CHILDREN’S SOCIAL INTERACTION IN INCLUSIVE EDUCATION - Marsudin, Riandi; Masseni; Nirwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this study is to investigate how teachers facilitate social interactions among children with autism within inclusive education practices at SDLB Inpres 73 Malaengkedi in Sorong City. This study is based on a sociocultural perspective, emphasizing that social interaction is developed through socially mediated experiences rather than solely through the child's individual abilities. A significant amount of research on inclusive education has focused on structural elements such as curriculum adaptations and policy implementations. However, there has been comparatively less attention on how teachers engage in social mediation during daily classroom interactions. This study employs a qualitative approach, utilizing a case study design that includes 13 informants: 1 school principal, 7 teachers, and 5 parents. Data were collected through participant observation, in-depth interviews, and documentation. The data were then analyzed thematically using NVivo version 14. The findings indicate that teachers act as primary social mediators through three main mechanisms: collaborative interaction strategies, enhancement of interpersonal communication, and promotion of peer acceptance. These practices facilitate the gradual development of interpersonal communication, classroom participation, and social engagement within an inclusive learning environment for children with autism. This study argues that the social interactions of children with autism in inclusive education do not occur automatically through formal inclusion systems. Instead, teachers' ongoing social mediation practices in daily learning activities are crucial in shaping these interactions.